Implementasi Filsafat Agama dalam Pendidikan Islam: Membangun Karakter dan Kedalaman Spiritual Melalui Pembelajaran Agama Islam di Perguruan Tinggi Umum - Aceng Badruzzaman; Muhammad Guntur Alting (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Religious philosophy and Islamic education are two fields that are interrelated and have a strong influence on shaping the worldview and values of Muslim society. The relationship between religious philosophy and Islamic education is very close. Religious philosophy provides a deep rationale for religious teachings, while Islamic education aims to transfer this understanding to future generations. Through Islamic education, students are given the opportunity to reflect on and understand the concepts of religious philosophy in real-life contexts. Learning the Islamic religion in public universities has an important role in shaping the character and spiritual depth of students. One approach that can be used to achieve this goal is the implementation of religious philosophy in Islamic religious learning. The implementation of religious philosophy in Islamic religious learning can help students understand religious teachings holistically. This can be done by studying sacred texts, religious traditions, and the thoughts of religious figures critically and in depth. In this way, students can develop a more comprehensive understanding of religious teachings and how these teachings can be applied in everyday life.